2004
DOI: 10.1016/j.virol.2004.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against the extracellular enveloped virus B5R protein are mainly responsible for the EEV neutralizing capacity of vaccinia immune globulin

Abstract: In the event of smallpox bioterrorism, widespread vaccination may be required. Vaccinia immune globulin (VIG) has been used to treat complications from the smallpox vaccine. While the potency of VIG was defined by its ability to neutralize intracellular mature virus, a second form of vaccinia called the extracellular enveloped virus (EEV) is critical for virus spread in the host. The B5R-protein is one of many EEV-specific proteins. Immunoprecipitation and ELISA revealed that VIG recognizes the B5R-protein. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
96
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 24 publications
8
96
2
1
Order By: Relevance
“…Recombinant B5 protein [11,14] as well as antibodies to B5 [18,19] can provide protection in the VACV mouse pneumonia model. In addition, B5 is the major target of EV neutralizing antibody in human VACV immune globulin [61], though antibody to B5 is not necessarily the most protective in vivo. Also, VACV B5 has a slightly greater amino acid identity (96%) to the MPXV homolog than VACV A33, which has 93% identity.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant B5 protein [11,14] as well as antibodies to B5 [18,19] can provide protection in the VACV mouse pneumonia model. In addition, B5 is the major target of EV neutralizing antibody in human VACV immune globulin [61], though antibody to B5 is not necessarily the most protective in vivo. Also, VACV B5 has a slightly greater amino acid identity (96%) to the MPXV homolog than VACV A33, which has 93% identity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that anti-B5 in VIG was responsible for most of the neutralizing activity against EV as measured by a plaque reduction assay (21). To date, rat and mouse anti-B5 neutralizing mAbs have been reported (20,22), and the epitopes recognized by mouse mAbs have been mapped to the border of SCR1-SCR2 and͞or the stalk of B5 (20).…”
mentioning
confidence: 99%
“…For example, passive immunization with antibodies to the EV proteins A33 and B5 is protective (42). Of the two, however, only the anti-B5 antibody neutralizes EV (6). Thus, the present and previous findings raise questions regarding the basis of protection by antibody and whether it occurs by direct virus neutralization or involves complement and Fc-receptor interactions.…”
Section: Discussionmentioning
confidence: 58%